10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Individuals living with chronic illness commonly experience co-occurring physical, psychological, and existential symptoms that cluster and reinforce one another, contributing to functional decline and distress. Yet, frailty and existential distress have rarely been examined alongside psychological and physical symptoms, and few studies have mapped how these symptoms interrelate across chronic conditions. This study used baseline patient-reported outcome measures (PROMs) from the eMPower randomized controlled trial to examine interconnections among symptoms across physical, psychological, and existential domains in adults living with chronic medical conditions. Adults aged ≥18 years (n = 825) were enrolled in the 12-week eMPower digital mind-body program (breathwork/meditation practices, movement, psychology-based coping skills curriculum based on acceptance and commitment therapy (ACT)). Baseline PROMs included the Hospital Anxiety and Depression Scale (HADS), Modified Fatigue Impact Scale (MFIS), EQ-5D-5L, SF-12, Edmonton Frail Scale Acute Care version (EFS-AC), online Fried Frailty Phenotype (online FFP), Demoralization Scale-II (DS-II), and PROMIS Sleep Disturbance SF-8a. Network analysis of pooled baseline data using LASSO-regularized partial correlations identified clusters and central symptoms. Participants had a mean age 55.6 ± 12.7 years and were predominantly female (84%). Across the cohort, symptom burden was high, frailty was prevalent, and quality of life was impaired. Network analysis identified three clusters: (i) mental health; (ii) fatigue and frailty; and (iii) quality of life, with physical fatigue emerging as the most central node linking psychological and functional domains. These findings suggest that fatigue, demoralization, and frailty are interconnected drivers of symptom burden in chronic illness. Targeting fatigue may represent an important strategy for improving mental health and functional outcomes in people living with chronic medical conditions.